Effectiveness Of Canadian Bleeding Scores (CAN BLEED) - Ekan faozi; Dini Ika Susanti; Luluk Purnomo (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2023)
Data from World Health Organization (WHO) shows that cases of internal bleeding due to accidents are 5.8 million deaths per year worldwide (Dahlan et al., 2021). Early awareness of internal bleeding is very important so that nurses can immediately take anticipation to prevent unwanted things(Damayanti, 2022). This literature study aims to determine the effectiveness of the CAN BLEED score for early detection of internal bleeding emergencies in trauma cases. The research method uses a literature review study design using PICOS. Article search through publish or perish 8 application with keywords "early detection AND internal bleeding AND trauma" from Pubmed, Crossref, and Google Scholar search databases based on the year of publication 2018-2022. The results of the article search found 4 articles relevant to the main topic. The results showed Canadian Bleeding (CAN BLEED) score is effective for determining internal bleeding in trauma cases.